Effects of non-pharmacological and non-surgical interventions on health outcomes in systemic sclerosis: protocol for a living systematic review. Issue 5 (4th May 2021) - Discepola, Marie-Nicole; Carboni-Jiménez, Andrea; Kwakkenbos, Linda; Henry, Richard S; Boruff, Jill; Krishnan, Ankur; Boström, Carina; Culos-Reed, S Nicole; Hudson, Marie; Leader, David M; Mattsson, Malin; Mouthon, Luc; et al.
Abstract : Introduction: Systemic sclerosis (SSc; scleroderma) is a rare, chronic, autoimmune disease with a high level of burden, a significant impact on the ability to carry out daily activities, and a considerable negative impact on health-related quality of life. Non-pharmacological interventions could be provided to potentially improve mental and physical health outcomes. However, the effectiveness of non-pharmacological interventions on health and well-being among individuals with SSc has not been well established. The proposed living systematic review aims to identify and evaluate randomised controlled trial (RCT) evidence on the effectiveness of non-pharmacological and non-surgical interventions on mental and physical health outcomes and on the delivery of such services in SSc. Methods and analysis: Eligible studies will be RCTs that examine non-pharmacological and non-surgical interventions aimed at improving health outcomes among individuals with SSc or the delivery of services intended to improve healthcare or support of people with SSc (eg, support groups). All RCTs included in a previous systematic review that sought studies published between 1990 and March 2014 will be evaluated for inclusion. Additional trials will be sought from January 2014 onwards using a similar, augmented search strategy developed by a health sciences librarian. We will search the MEDLINE, Embase, CINAHL, PsycINFO, Cochrane Library and Web of Science databases and will not restrict by language. Two independent reviewers will determine the eligibility of identified RCTs and will extract data using a prespecified standardised form in DistillerSR. Meta-analyses will be considered if ≥2 eligible RCTs report similar non-pharmacological interventions and comparable health outcomes. We will conduct a qualitative synthesis for interventions that cannot be synthesised via meta-analysis. Ethics and dissemination: We will post initial and ongoing results via a website, publish results periodically via peer-reviewed journal publication, and present results at patient-oriented events. PROSPERO registration number: CRD42020219914.